HUBUNGAN PERSEPSI HARAPAN ORANG TUA TERHADAP PENGAMBILAN JURUSAN SMA/SMK SISWA KELAS VIII SMPN 1 BALONGBENDO - Aji Rajasa, Pief Gustida (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2020)
AbstractÂ Â  This research is the result of observations we made in the field about the perspective of elections in high school / vocational high school students held by parents' expectations. The purpose of this study was to examine the expectations of parents of eighth grade students of SMP Negeri 1 Balongbendo in choosing majors in high school / vocational school. This research is a quantitative study using a correlational descriptive method using data collection techniques in the form of a questionnaire with a total of 22 question items and using a Likert scale rating scale. The population of this research is students of class VIII of SMP Negeri 1 Balongbendo taken as a sample with a total sample of 35 students. An interesting result is the child's perception of expectations that have been adjusted to the selection of high school / vocational school majors in junior high school students.Keywords: Parental expectations, career, outlook, decision making.